2018
DOI: 10.1002/elan.201800103
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical On‐site Amino Acids Detection of Maple Syrup Urine Disease Using Vertically Aligned Nickel Nanowires

Abstract: In this work, vertically aligned nickel nanowires‐based electrochemical sensors (v‐NiNWs) for rapid detection of branched‐chain amino acids for a non‐invasive screening of maple syrup urine disease (MSUD), are proposed. v‐NiNWs meet the required features for decentralized clinical diagnosis: easy to operate, fast sensor response and short total analysis times (5 min), as well as low sample consumption (250 ml). The analytical characteristics (for leucine as representative branched‐chain amino acid in MSUD) suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The use of metal nanowires (NWs) gives some advantages in clinical diagnosis such as simplicity, rapid sensor response and short total analysis time, and low sample consumption. Recently, García-Carmona et al [77] demonstrated the fabrication of vertically aligned nickel nanowires-based electrochemical sensors (v-NiNWs) for fast determination of b AA, aiming to noninvasive screening of MSUD. v-NiNWs.…”
Section: Metal Nanoparticles and B Aa Electrochemical (Bio)sensingmentioning
confidence: 99%
“…The use of metal nanowires (NWs) gives some advantages in clinical diagnosis such as simplicity, rapid sensor response and short total analysis time, and low sample consumption. Recently, García-Carmona et al [77] demonstrated the fabrication of vertically aligned nickel nanowires-based electrochemical sensors (v-NiNWs) for fast determination of b AA, aiming to noninvasive screening of MSUD. v-NiNWs.…”
Section: Metal Nanoparticles and B Aa Electrochemical (Bio)sensingmentioning
confidence: 99%
“…The analysis of several diseases by non‐invasive methods is a good alternative in clinical analysis since it implies less discomfort for the patient. For this type of analysis, the main matrices used are urine and saliva . Among the compounds that act as biomarkers for disease diagnosis are UA, creatinine, and glucose, which can be found in urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid analysis is an important technique in many pharmaceutical, medical, chemical, food research, and industrial areas [1][2][3]. Thus far, various analytical methods have been proposed to determine amino acids, including high-performance liquid chromatography, capillary electrophoresis, enzyme assay, and chemical sensors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Usually, because of the weak light-absorptive property of amino acids, pre-or post-column derivatization with an appropriate labeling reagent is performed for determining amino acids with sensitivity and selectivity in HPLC with UV detection (HPLC-UV) and fluorescence detection (HPLC-FL) systems [9,10].…”
Section: Introductionmentioning
confidence: 99%